Controllable organic magnetoresistance in polyaniline coated poly(p-phenylene-2, 6-benzobisoxazole) short fibers. Issue 68 (29th July 2019) - Gu, Hongbo; Xu, Xiaojiang; Cai, Jingyi; Wei, Suying; Wei, Huige; Liu, Hu; Young, David P.; Shao, Qian; Wu, Shide; Ding, Tao; Guo, Zhanhu
Abstract : A controllable organic magnetoresistance in polyaniline coated poly( p -phenylene-2, 6-benzobisoxazole) short fibers is firstly reported and theoretically analyzed. Abstract : Herein, we first report a tunable organic magnetoresistance (OMAR) effect in polyaniline (PANI) coated acid treated poly( p -phenylene-2, 6-benzobisoxazole) (t-PBO) short fibers. This unique OMAR is interpreted using the paramagnetic nature of PBO molecules combined with the localization length a 0 calculated from the wave-function shrinkage model and forward interference model.